Determinants of Physics Achievement in Modular Distance Education Among Rural Filipino Learners: An Empirical Analysis - Purigay, John Paul D.; Cadiente, Rosemarie A.; Valderama, Julius S.; Rivera, Daisy V.; Lopez, Edison B. (Journal of Teaching and Learning, 2026)
Persistent educational inequities continue to hinder physics achievement among rural learners, particularly within modular distance education implemented in Philippine public schools. This study is among the first empirical investigations to quantitatively examine equity-related factors influencing Grade 10 students’ achievement in physics in a modular learning context, addressing a gap in subjectspecific equity research. Anchored in Sen’s Capability Approach and the Organization for Economic Co-operation and Development’s framework on educational equity, the study analyzed the influence of access to physics learning materials, parental and teacher support, and learners’ perceptions of fairness and inclusion on academic performance in physics. A correlational research design was employed involving 312 Grade 10 students from selected rural public secondary schools. Data were collected using a validated equity-focused questionnaire and standardized physics grades. Results revealed significant positive relationships between physics achievement and access to learning materials, home-based learning support, and teacher feedback. Multiple regression analysis indicated that access to learning materials and parental support significantly predicted physics achievement. Group comparisons revealed significant differences by household income and geographic accessibility, while gender differences were not significant. These findings support equity-responsive policies that prioritize resource provision and instructional strategies that strengthen teacher feedback and home–school collaboration in modular Physics education.